In vitro digestibility of cyclopropane fatty acids in Grana Padano cheese: A study combining 1H NMR and GC-MS techniques. (November 2018) - Lolli, Veronica; Dall'Asta, Margherita; Del Rio, Daniele; Caligiani, Augusta
Abstract: Cyclopropane fatty acids (CPFA), like dihydrosterculic and lactobacillic acid, are unusual fatty acids found in microorganisms, seed oils of some sub-tropical plants, and protozoa. Recently, these molecules were detected in milk and dairy products, as well as in meat and fish. To the best of our knowledge, only a few studies have documented their presence and relevance in animals and humans. In the present work, the digestibility of CPFA from Grana Padano cheese was evaluated through an in vitro digestion model. Two different complementary analytical techniques ( 1 HNMR and GC-MS) were applied for better evaluating the presence of CPFA in raw and digested matrices. Results showed that CPFA were released from tri-O-acylglycerols, and that the cyclopropane ring was not degraded, indicating their stability and potential bioaccessibility after digestion in the present model. 1 H NMR and GC-MS analysis of the digested samples also provided comprehensive and complementary information for studying qualitatively and quantitatively the hydrolysis level of these fatty acids in complex lipid matrices. Highlights: The digestibility of CPFA from Grana Padano cheese was studied by an in vitro simulated gastrointestinal digestion. The degree of lipolysis after digestion has been evaluated by 1 HNMR and GC-MS. The in vitro gastrointestinal model adopted was suitable for lipid-rich foods. Results showed the stability and digestibility of CPFA after in vitro digestion.